Use of Transcriptomic Analyses to Elucidate the Mechanism Governing Nodal Root Development in Eremochloa ophiuroides (Munro) Hack. - Wang, Rui; Zhao, Haoyan; Guo, Hailin; Zong, Junqin; Li, Jianjian; Wang, Haoran; Liu, Jianxiu; Wang, Jingjing (Frontiers in Plant Science, 2021)
Centipedegrass [Eremochloa ophiuroides (Munro) Hack.] is a perennial warm-season grass that originated in China, and its speed of nodal rooting is important for lawn establishment. In our study, centipedegrass nodal rooting ability was limited by node aging. Transcriptome sequencing of nodal roots after 0, 2, 4 and 8 d of water culture were performed to investigate the molecular mechanisms of root development. GO enrichment and KEGG pathway analyses of DEGs indicated that plant hormone signal transduction and transcription factors might play important roles in centipedegrass nodal root growth. Among them, E3 ubiquitin-protein ligases participated in multiple hormone signal transduction pathways and interacted with transcription factors. Futhermore, an E3 ubiquitin protein ligase EoSINAT5 overexpressed in rice resulted in longer roots and more numerous root tips, while knockout of LOC_Os07g46560 (the homologous gene of EoSINAT5 in rice) resulted in shorter roots and fewer root tips. These results indicated that EoSINAT5 and its homologous gene are able to promote nodal root development. This research presents the transcriptomic analyses of centipedegrass nodal roots, and may contribute to elucidating the mechanism governing the development of nodal roots and facilitates the use of molecular breeding in improving rooting ability.